GREEN SUPPLY CHAIN MANAGEMENT IN THE ENERGY SECTOR BASED ON THE MULTI-CRITERIA MODEL KTT GSCM - Matvieieva, Yuliia; Opanasiuk, Yuliia; Vakulenko, Ihor (Socio-economic relations in the digital society, 2023)
The application of multi-criteria decision-making methods allows to reduce ambiguity, inaccuracy, and uncertainty in the development of transfer processes and the development of innovations for energy. The article provides a literature review of the impact of innovative technologies on the condition of energy development. A bibliographic analysis was carried out on the basis of the Scopus database, Vosviewer software and Google Trends. The research summarizes the scientific and methodological approaches to the application of KTTGS. The author’s KTTGSCM model for energy innovations was developed in the article. The model can be used to evaluate and analyze the process of knowledge and technology transfer in a green supply chain to increase efficiency and reduce environmental impact. The study is designed to improve the understanding of the KTTGSCM model and its application in the green supply chains management of the energy sector. The purpose of the study is to generalize the scientific and theoretical provisions of the features of the multi-criteria KTTGSC model. The article develops a mechanism for the knowledge and technology transfer that influence of innovation process in green supply chain management, based on the KTTGSCM model.